Pattern of reported tuberculosis cases in iran 2009-2010. - Jafar Hassan Zadeh; Mahshid Nasehi; Abbas Rezaianzadeh; Hamidreza Tabatabaee; Abdolreza Rajaeifard; Ebrahim Ghaderi (Tehran University of Medical Sciences, 2013)
Cooperation of all health sectors and early diagnosis of the disease are the key factors for controlling tuberculosis. This study assesses the patterns of reported tuberculosis cases in Iran.This was a cross sectional study. Tuberculosis cases were defined according to World Health Organization and Iran's national TB guidelines. Final data were prepared for analysis using SPSS16 software.Public hospitals, public and private outpatient clinics reported 4111 (39.1%), 3007 (28.6%) and 2839 (27%) cases of TB, respectively. The highest number of reported TB cases was from the public healthcare system. One third of TB cases were reported by private outpatient clinics.It is essential to make a plan such as public-private mix model in Iran. Because of high coverage of private physicians in our country and even in rural areas, it is quite necessary to involve private system in tuberculosis program.